Impact of bariatric surgery on cardiovascular outcomes and mortality: a population-based cohort study. Issue 4 (21st January 2020) - Singh, P; Subramanian, A; Adderley, N; Gokhale, K; Singhal, R; Bellary, S; Nirantharakumar, K; Tahrani, A A
Abstract: Background: Cohort studies have shown that bariatric surgery may reduce the incidence of and mortality from cardiovascular disease (CVD), but studies using real-world data are limited. This study examined the impact of bariatric surgery on incident CVD, hypertension and atrial fibrillation, and all-cause mortality. Methods: A retrospective, matched, controlled cohort study of The Health Improvement Network primary care database (from 1 January 1990 to 31 January 2018) was performed (approximately 6 per cent of the UK population). Adults with a BMI of 30 kg/m 2 or above who did not have gastric cancer were included as the exposed group. Each exposed patient, who had undergone bariatric surgery, was matched for age, sex, BMI and presence of type 2 diabetes mellitus (T2DM) with two controls who had not had bariatric surgery. Results: A total of 5170 exposed and 9995 control participants were included; their mean(s.d.) age was 45·3(10·5) years and 21·5 per cent (3265 of 15 165 participants) had T2DM. Median follow-up was 3·9 (i.q.r. 1·8– 6·4) years. Mean(s.d.) percentage weight loss was 20·0(13·2) and 0·8(9·5) per cent in exposed and control groups respectively. Overall, bariatric surgery was not associated with a significantly lower CVD risk (adjusted hazard ratio (HR) 0·80; 95 per cent c.i. 0·62 to 1·02; P  = 0·074). Only in the gastric bypass group was a significant impact on CVD observed (HR 0·53, 0·34 to 0·81; P  = 0·003). Bariatric surgery was associated with significant reduction in all-cause mortality (adjusted HR 0·70, 0·55 to 0·89; P  = 0·004), hypertension (adjusted HR 0·41, 0·34 to 0·50; P < 0·001) and heart failure (adjusted HR 0·57, 0·34 to 0·96; P  = 0·033). Outcomes were similar in patients with and those without T2DM (exposed versus controls), except for incident atrial fibrillation, which was reduced in the T2DM group. Conclusion: Bariatric surgery is associated with a reduced risk of hypertension, heart failure and mortality, compared with routine care. Gastric bypass was associated with reduced risk of CVD compared to routine care. Graphical Abstract: Bariatric surgery is associated with a reduction in mortality, incident cardiovascular disease (CVD), heart failure and hypertension compared with routine care in patients with and without type 2 diabetes mellitus (T2DM). IHD, ischaemic heart disease; TIA, transient ischaemic attack. Associated with better survival